2008
DOI: 10.1213/ane.0b013e318185cf73
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Attenuates Late but Not Early Postoperative Pain After Thyroidectomy with Superficial Cervical Plexus Block

Abstract: Oral preoperative administration of gabapentin did not modify immediate pain management in thyroidectomy patients receiving SCPB, but prevented delayed neuropathic pain at 6 mo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 26 publications
1
79
2
3
Order By: Relevance
“…Although the conclusion from Chaparro et al was that that gabapentin does not reduce the incidence of CPSP, the small sample size of the studies limits these interpretations, especially when considering that these results derive from heterogeneous surgical procedures. Brogly et al [28] found that 1200 mg of gabapentin administered before surgery reduced chronic but not early acute postoperative pain following superficial cervical plexus block [28]. The lack of standardized gabapentin doses between studies may have contributed to inconsistencies in the drug's efficacy at reducing the incidence and severity of CPSP.…”
Section: Gabapentinmentioning
confidence: 99%
“…Although the conclusion from Chaparro et al was that that gabapentin does not reduce the incidence of CPSP, the small sample size of the studies limits these interpretations, especially when considering that these results derive from heterogeneous surgical procedures. Brogly et al [28] found that 1200 mg of gabapentin administered before surgery reduced chronic but not early acute postoperative pain following superficial cervical plexus block [28]. The lack of standardized gabapentin doses between studies may have contributed to inconsistencies in the drug's efficacy at reducing the incidence and severity of CPSP.…”
Section: Gabapentinmentioning
confidence: 99%
“…All the RCTs administered pre-emptive gabapentin or its combination with other analgesic drugs. Thirteen of all presented RCTs evaluated pre (10 RCTs) [50,52,54,56,58,61,63,64,67,68] and both pre/post-operative (3 RCTs) [48,49,59] doses of GBP alone vs placebo patients. Eight RCTs studied gabapentin in confront with other analgesics (dexamethasone, lornoxicam, celecoxib, rofecoxib, acetaminophen, clonidine); five of them used only pre-emptive analgesia [53,55,57,62,65] and 3 considered both pre and post-operative mixture administration [47,51,66].…”
Section: Gabapentin Rctsmentioning
confidence: 99%
“…No studies established the optimal post surgical GBP treatment duration. Pain assessment has been performed using a Visual Analogue Scale (VAS) in 18 RCTs [48,50,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], meanwhile three studies used a 11-point [47,49] or 4-point [51] Verbal Rating Scale (VRS). One study did not consider pain evaluation but only postoperative PCA fentanyl consump-tion, focusing the attention to the anti-emetic gabapentin effects [68].…”
Section: Gabapentin Rctsmentioning
confidence: 99%
“…17 The current report only assessed patients until six months of follow-up. However, evaluation after six months would most likely not find any differences in POCP, given that the pain intensity was already mild in both groups at six months.…”
Section: Resultsmentioning
confidence: 99%